O Sentido de liberdade na sociedade capitalista a partir da perspectiva marxiana - Farias, Drielly Tenório Marinho (2017)
The present study seeks to understand the sense of freedom in the capitalist mode of production from the Marxian perspective. It is a research that rescues the relation between work and freedom, from the beginnings to the current sociability, and the importance that the sense of freedom has for the functioning of the capital system. It is perceived that the capitalist mode of production propagates that its basic characteristic is the freedom to sell in the market. However, what would be the freedom of man if his existence depends entirely on the sale of his labor power to the capitalist. The methodology used was bibliographic research.